2013
DOI: 10.1111/are.12130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary taurine levels on epidermal thickness and scale loss in red sea bream,Pagrus major

Abstract: Taurine is often added to artificial fish diets to compensate for a reduction in fish meal (FM). However, the taurine content of FM-based diets is typically lower than in diets consisting of raw fish, even in diets where FM is the only protein source. We evaluated the effects of dietary taurine in FM-based diets on epidermal thickness and scale detachability in red sea bream Pagrus major. We compared the effect of diets containing 0% (control), 0.3% (Tau-0.3%), 0.6% (Tau-0.6%) and 1.0% (Tau-1.0%) taurine. Red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The osmoregulatory effect of taurine has been highlighted in fish and other species (Huxtable, 1992;Takagi et al, 2006a). In fish, indirect osmoregulatory action was suggested by an increase in skin thickness and condition in fish fed taurine-supplemented diets (Kato et al, 2014). Also, since other α-amino acids such as glycine and arginine can also participate in cellular osmoregulation in fish (Li et al, 2009), it could be hypothesized that taurine spares these amino acid which then become available for protein synthesis or energy production.…”
Section: Effects On Growthmentioning
confidence: 99%
“…The osmoregulatory effect of taurine has been highlighted in fish and other species (Huxtable, 1992;Takagi et al, 2006a). In fish, indirect osmoregulatory action was suggested by an increase in skin thickness and condition in fish fed taurine-supplemented diets (Kato et al, 2014). Also, since other α-amino acids such as glycine and arginine can also participate in cellular osmoregulation in fish (Li et al, 2009), it could be hypothesized that taurine spares these amino acid which then become available for protein synthesis or energy production.…”
Section: Effects On Growthmentioning
confidence: 99%
“…Nutrient deficiencies such as essential amino acids, taurine and phospholipids lead to the unsuccessful fish meal replacement especially for marine carnivorous fish (Koven, Peduel, Gada, Nixon & Ucko, ; Sales, ). However, in the formulation of soybean products‐based feed where low fish meal was used, studies have shown that the supplementation of ingredients such as corn gluten meal, taurine and lecithin is important (Biswas et al., ; Deng et al., ; Kato et al., ; Luo et al., ; Pereira & Oliva‐Teles, ; Sevgili et al., ). Corn gluten meal has high availability of amino acid to fish such as methionine and lysine and was suggested to improve the imbalance of essential amino acid in soybean meal (NRC ).…”
Section: Introductionmentioning
confidence: 99%
“…Taurine is very important as it has an important role especially in osmoregulation, lipid absorption and contributing to visual, neural and muscular function (Johnson et al., ; Koven et al., ). The supplementation of taurine was suggested to improve the feed utilization and physiological abnormalities of fish when fed with low fish meal feed (Kato et al., ) while lecithin can provide more sources of phospholipid in soybean meal‐based feed (Tocher, Bendiksen, Campbell & Bell, ). In addition, the supplementation of lecithin helps to improve lipid emulsification and acid digestion in the intestine of fish after consumption (Tocher et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been considered as an essential nutrient for many fish species due to their limited taurine biosynthesis abilities (Takagi, Murata, Goto, Endo, Yamashita & Ukawa 2008;Li, Mai, Trushenski & Wu 2009;Espe & Holen 2013;Lim, Oh, Khosravi, Cha, Park, Kim & Lee 2013;Salze & Davis 2015). Taurine has multiple physiological functions in fish, such as growth stimulation (Lunger, McLean, Gaylord, Kuhn & Craig 2007), osmoregulation (Takagi, Murata, Goto, Hayashi, Hatate, Endo, Yamashita & Ukawa 2006a;Kato, Yamamoto, Peerapon, Fukada, Biswas, Yamamoto, Takii & Miyashita 2014), bile salt conjugation (Kim, Matsunari, Takeuchi, Yokoyama, Murata & Ishihara 2007), antioxidant defence (Espe & Holen 2013) and larvae development (Pinto, Figueira, Ribeiro, Y ufera, Dinis & Aragão 2010).…”
Section: Introductionmentioning
confidence: 99%